ANALISIS KUALITAS REPAIR WELDING CAST WHEEL ALUMINIUM MENGGUNAKAN METODE PENGELASAN OKSI-ASETILIN DENGAN PERLAKUAN PREHEATING DAN POST WELD HEAT TREATMENT - Aftoni Heri Septian Pamungkas; Budi Harjanto; Indah Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The aims of this research are to find out chemical composition, micro structure, the hardness level, and the strength impact of raw material and after welding using preheating and post weld heat treatment on cast wheel aluminum. Those data were analyzed using comparative descriptive method. The equipments used for measuring the chemical composition, microstructure, the hardness level, and the strength impact are as following: Spectrometer Metal Scan, Olympus Metallurgy Microscope, Vikers Hardness Tester and Charpy Tester. Based on the experiment results, it can be concluded that the chemical composition of the main constituent of cast wheel aluminum is 7,41% Si, which can be categorized in the aluminum alloy AA4343 series. The experiment results showed a decrease in the extent of the microstructure of primary Si phase after welding. Si primary phase were spread well around the surface of 12Î±